Strategies of Islamic Religious Education Teachers in Instilling Moral Values in the Digital Era: A Study at Madrasah Ibtidaiyah Thoriqotul Hidayah Taman Laren, Lamongan Regency - Istichoroh, Lailatul; Hamid, Ahmad Munir; Nihayatus, Hurin In (Universitas Islam Negeri Sumatera Utara, 2025)
The rapid development of digital technology has had a significant impact on the world of education, including instilling moral values. One of the main challenges for Islamic Religious Education (PAI) teachers is how to integrate these values amidst the rapid flow of digital information. This research aims to identify and analyze the strategies implemented by PAI teachers at MI Thoriqotul Hidayah Taman Laren, Lamongan Regency in instilling moral values in students in the digital era. Using a qualitative descriptive approach, data was obtained through observation, interviews and documentation. The research results show that teachers apply strategies such as the use of technology-based media, religious project-based learning, and character building through extracurricular activities with a moral aspect. Wise use of technology has been proven to be able to increase the effectiveness of instilling moral values according to Islamic teachings. This research contributes to the development of PAI learning strategies that are adaptive to digital developments without ignoring the essence of character education.